Prevalence of Occupational Ocular Injury and Associated Factors Among Small-Scale Industry Workers in Gondar Town, Northwest Ethiopia, 2019 - Mengistu HG; Alemu DS; Alimaw YA; Yibekal BT (Clinical Optometry, 2021)
Hirut Gebremeskel Mengistu,1 Destaye Shiferaw Alemu,2 Yezinash Addis Alimaw,2 Betelhem Temesgen Yibekal2 1Tertiary Eye Care and Training Center, University of Gondar Comprehensive Specialized Hospital, Gondar Town, Ethiopia; 2Department of Optometry, School of Medicine, College of Medicine and Health Science, University of Gondar Comprehensive Specialized Hospital, Gondar Town, EthiopiaCorrespondence: Yezinash Addis Alimaw Email yezaddi@gmail.comPurpose: To assess the prevalence of occupational ocular injury and associated factors among small-scale industry workers in Gondar town, Northwest Ethiopia.Methods and Materials: Institution-based cross-sectional study was conducted on 542 manufacturing and construction workers in Gondar town from April 23 to May 4, 2019. A pre-tested questionnaire was used to collect data using face-to-face interview. Binary logistic regression was used to identify factors associated with occupational ocular injury.Results: A total of 542 small-scale industry workers participated with a 95.1% response rate. The prevalence of occupational ocular injury was 31.4% (95% CI, 27.2– 35.5). Employment pattern (temporary workers) (AOR: 1.84, 95% CI: 1.14– 2.95), health and safety training (AOR: 2.22, 95% CI: 1.06– 4.66), non-use of eye safety device (AOR: 7.43, 95% CI: 4.44– 12.43), and job category (woodwork (AOR: 0.56, 95% CI: 0.32– 0.97)), and brickwork (AOR: 2.19, 95% CI: 1.08– 7.21) had statistically significant with occupational ocular injury.Conclusion: This study showed the prevalence of occupational ocular injury among small-scale industry workers was 31.4%. Iron chips are the most common agent responsible for the injury. Type of employment, having health and safety training, use of eye safety devices, and job category had a significant association with occupational ocular injury.Keywords: occupational ocular injury, small scale industry workers, Gondar, Ethiopia